Teachers` creativity and innovation: the key to educational change = Kreatywność nauczycieli i innowacja: klucz do zmian w edukacji - Capelo, Maria Regina Teixeira Ferreira; Costa Varela, John Miguel; Diaz, Noemí Serrano; Jardim, Maria Helena Gonçalves (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Globalization and technological revolution have transformed economic, cultural and social processes around the world. Modern societies require that teachers introduce new pedagogical practices to improve the quality of education. An overview of theoretical contributions suggests that creativity and innovation are inseparable and interdependent allies in emancipatory education. That is why it is important for education systems to employ adequately trained and well-paid teachers and officials who create an environment conductive to creativity and innovation.
Keywords: creativity; education; innovation; teachers; kreatywność; edukacja; innowacja; nauczyciele